Comparison of Cyclic Fatigue Resistance of Two Different Rotary NiTi Instruments (An In-Vitro Study) - Dalia Abd allah; mohamed Nagy; Tariq Yehia (Ain Shams University, Faculty of Dentistry, 2024)
Aim: The aim of this study was to compare the dynamic cyclic fatigue resistance of M3-ProGold files and Pepsi Gold Files.Materials and methods: Eighty files of size 25/.06 of M3 Pro Gold files and Pepsi Gold files (each n = 40) were evaluated for dynamic cyclic fatigue resistance inside two artificial stainless steel canals with 2 different radii [(60 curvature, 3 mm radius) and (60 curvature, 5 mm radius)] at body temperature while submerged in distilled water at 37 ° ± 1 °C. The NCF (number of cycles to failure) was calculated. The data of NCF were analyzed using ANOVA and Tukey post hoc tests (P ≤ 0 .05). Results: The Pepsi Gold files had a significantly higher number of cycles to failure than the M3 Pro Gold files in both canal radii at body temperature. Conclusion: Pepsi Gold files have greater resistance to cyclic fatigue than M3 Pro Gold files.